Can Cosplay in Story-Telling Improve Student’s Listening Skill in Listening to Stories Learning? - Valiant, Diksi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The purpose of this study is to know whether cosplay in story telling can improve students' listening skills. Listening is one of the very important part of a language lesson. Listening is one of the essential skills that will become the foundation of other language developments. Listening skill will affect the ability to speak, read, and write. Therefore listening skills need to be taught to students in elementary school level. One of the obstacles in listening learning, especially stories, is the difficulty of maintaining the student's concentration range. Therefore, a special strategy is needed to increase students' concentration when listening to a story. In an observation at school, a teacher looks